The Effect of Small Games on Learning Overhead Serve and Receiving in Volleyball For Secondary School Students - khadim, Emad; Ahmed, Aftkhar (Journal of Physical Education, 2019)
The aim of this study was to identify the effect of the precise exercises used to rehabilitate ankle sprain. The researcher used the tests of the range of the ankle joint movement, the strength of the muscles working on it and motor balance. Rehabilitation exercises were applied to six footballers in the first class clubs with sprained ankle .the results showed that there were statistically significant differences between thepre and post-tests in the research variables and in good turn of the post test.the researchers have concluded that the use of specific exercises associated with therapeutic methods helped in the rehabilitation of the injured ankle joint of the football player and returns to training and competition.